A Zeeman slower for diatomic molecules. (12th April 2018) - Petzold, M; Kaebert, P; Gersema, P; Siercke, M; Ospelkaus, S
Abstract: We present a novel slowing scheme for beams of laser-coolable diatomic molecules reminiscent of Zeeman slowing of atomic beams. The scheme results in efficient compression of the one-dimensional velocity distribution to velocities trappable by magnetic or magneto-optical traps. We experimentally demonstrate our method in an atomic testbed and show an enhancement of flux below v  = 35 m s −1 by a factor of ≈20 compared to white light slowing. 3D Monte Carlo simulations performed to model the experiment show excellent agreement. We apply the same simulations to the prototype molecule 88 Sr 19 F and expect 15% of the initial flux to be continuously compressed in a narrow velocity window at around 10 m s −1 . This is the first experimentally shown continuous and dissipative slowing technique in molecule-like level structures, promising to provide the missing link for the preparation of large ultracold molecular ensembles.